Waste Concrete as a Substitute for Coarse Aggregate Materials for Compressive Strength of Concrete Fc' 20,75 MPa - Bobby Damara; Sugeng Dwi Hartantyo (Kadiri University, 2022)
Concrete from construction waste resulting from the construction of new infrastructure replacing old infrastructure can significantly impact the environment. Therefore, there is a need for the proper management of concrete waste. One of the uses of concrete waste is to use it as a coarse aggregate material in the manufacture of Concrete. Using waste concrete is obtaining a material that almost resembles coarse aggregate. This study aimed to determine the optimum content of Concrete with the addition of waste concrete as a substitute for coarse aggregate. This research refers to the standards of SNI and ASTM. The research was conducted by testing the waste concrete to determine whether it is suitable for coarse aggregate material. After that, the compressive strength was tested by curing for 28 days. This research was conducted with 3 samples with 0%, 50%, and 100% of the planned use of concrete waste with concrete compressive strength of Fc' 20,75 MPa. The results showed that the average compressive strength of the 50% concrete waste was 20.59 MPa, and the 100% concrete waste was 13.83 MPa. From these results, it can be seen that the most optimum content of substituted aggregate is a mixture variation of 50%, so the results of this study can be used as a reference in the utilization of recycled concrete waste as a raw material or a substitute for the composition of the concrete mixture.